2006
DOI: 10.1038/sj.mp.4001844
|View full text |Cite
|
Sign up to set email alerts
|

Changes in NMDA receptor subunits and interacting PSD proteins in dorsolateral prefrontal and anterior cingulate cortex indicate abnormal regional expression in schizophrenia

Abstract: Abnormal expression of the N-Methyl-D-Aspartate (NMDA) receptor and its interacting molecules of the postsynaptic density (PSD) are thought to be involved in the pathophysiology of schizophrenia. Frontal regions of neocortex including dorsolateral prefrontal (DLPFC) and anterior cingulate cortex (ACC) are essential for cognitive and behavioral functions that are affected in schizophrenia. In this study, we have measured protein expression of two alternatively spliced isoforms of the NR1 subunit (NR1 C2 and NR1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
119
3
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(138 citation statements)
references
References 81 publications
12
119
3
1
Order By: Relevance
“…Regional differences in molecular abnormalities in schizophrenia are consistently reported in the literature (Katsel et al, 2005a, b;Kristiansen et al, 2006Kristiansen et al, , 2010Oni-Orisan et al, 2008), and although the sets of changes we found differed by cortical region, each set is functionally similar, resulting in decreased signal integration in both regions. This differential expression pattern may be inherent to the physiological circuits and inputs for each region.…”
Section: Discussionsupporting
confidence: 71%
“…Regional differences in molecular abnormalities in schizophrenia are consistently reported in the literature (Katsel et al, 2005a, b;Kristiansen et al, 2006Kristiansen et al, , 2010Oni-Orisan et al, 2008), and although the sets of changes we found differed by cortical region, each set is functionally similar, resulting in decreased signal integration in both regions. This differential expression pattern may be inherent to the physiological circuits and inputs for each region.…”
Section: Discussionsupporting
confidence: 71%
“…The protein levels are determined not only by the level of the mRNA that codifies it and its translation rate, but also by the folding efficiency of the protein itself, posttranslational modifications, binding with other components to form protein complexes, and the rate of protein degradation. Some of these events could modify protein levels without a change in mRNA expression (You and Yin, 2000;Kristiansen et al, 2006). In summary, our data support that in schizophrenia and mood disorders, glutamate receptor expression is altered in the medial temporal lobe.…”
Section: Limitations Of the Studysupporting
confidence: 67%
“…In a smaller study (n ¼ 6 subjects with schizophrenia, n ¼ 10 controls) in situ hybridization analysis showed that the expression of PSD95 was significantly decreased in Brodmann area 9 of the prefrontal cortex but not in the hippocampus (Ohnuma et al, 2000). Using tissues from elderly subjects from the Bronx VA brain collection, PSD95 transcripts were increased, and PSD95 protein was decreased in the anterior cingulate cortex (Kristiansen et al, 2006). This finding was replicated in the ACC by the same group in a cohort with overlapping subjects, whereas no change in PSD95 protein was found in the DLPFC (Funk et al, 2009(Funk et al, , 2012.…”
Section: Data From Post-synaptic Density 95 (Psd95)mentioning
confidence: 99%